The Development of Writing Habitus: A Ten-Year Case Study of a Young Writer. (October 2014) - Compton-Lilly, Catherine
Peter, an African American writer from a low-income community, is followed across a 10-year period as he progresses from first grade through high school. Drawing on writing samples and interviews, the author identifies a set of interrelated dispositions that contribute to his development of habitus as a writer. This article considers Peter's developing writing abilities alongside these emerging dispositions that include (a) meeting school expectations for reading and writing, (b) being good in school and being a good student, (c) forming friendships and affiliations that involve reading and writing practices, and (d) crafting future goals related to writing. Future success as a professional writer was contingent on his writing abilities being recognized, valued, and taken up in contexts beyond high school. The author draw on Bourdieu's constructs of habitus and field to explore Peter's becoming a writer across time.